2021
DOI: 10.1080/2162402x.2021.1932365
|View full text |Cite
|
Sign up to set email alerts
|

DIMEimmune: Robust estimation of infiltrating lymphocytes in CNS tumors from DNA methylation profiles

Abstract: The interaction of CNS tumors with infiltrating lymphocytes plays an important role in their initiation and progression and might be related to therapeutic responses. Gene expression-based methods have been successfully used to characterize the tumor microenvironment. However, methylation data are now increasingly used for molecular diagnostics and there are currently only few methods to infer information about the microenvironment from this data type. Using an approach based on differential methylation and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 55 publications
3
17
0
Order By: Relevance
“…This phenomenon implies that estimating the TILs and endothelial cells can contribute to identifying the progression and prognosis of MB. A previous study showed that the DIME (Differential Methylation Analysis for immune Cell Estimation)-TIL score was a negative prognostic factor in MB ( 42 ), which laterally supported our hypothesis. Furthermore, tumor endothelial cells are required for tumor angiogenesis, which is crucial for tumor progression and metastasis ( 43 ).…”
Section: Discussionsupporting
confidence: 89%
“…This phenomenon implies that estimating the TILs and endothelial cells can contribute to identifying the progression and prognosis of MB. A previous study showed that the DIME (Differential Methylation Analysis for immune Cell Estimation)-TIL score was a negative prognostic factor in MB ( 42 ), which laterally supported our hypothesis. Furthermore, tumor endothelial cells are required for tumor angiogenesis, which is crucial for tumor progression and metastasis ( 43 ).…”
Section: Discussionsupporting
confidence: 89%
“…(I) Evaluation of the tumour microenvironment using immunohistochemistry showed focal clusters of CD8 (+) T cells both at diagnosis and relapse. (J) Estimates of CD8 infiltration using the DIME score using methylation data as described by Safaei et al [ 22 ] showed higher CD8 T‐cell scores for the index patient as compared with MMR‐proficient ependymomas ( p = 0.0087; Mann–Whitney test).…”
Section: Figurementioning
confidence: 99%
“…Algorithm like ESTIMATE, CIBERSORT or Microenvironment Cell Populations (MCP)-counter quantify immune and stromal cell populations based on defined marker gene expression signatures [ 55 , 56 , 57 ]. Further progress on deconvolution approaches was made on genome-wide DNA methylation data, introducing MeTIL, MethylCIBERSORT and DIMEimmune [ 58 , 59 , 60 ].…”
Section: Targeting Immune Cells In Pediatric Brain Tumorsmentioning
confidence: 99%
“…Lastly, significant prognostic relationships were found in infant SHH-MB (B cell amount significantly greater), low-risk Gr.3-MB (Treg significantly associated with poor survival) and pediatric HGG (monocytes significantly enriched in tumors with MAPK mutations) [ 21 ]. Safaei et al [ 60 ] developed DIMEimmune for differential methylation analysis for immune cell estimation [ 60 ]. This study calculated estimations of CD4+, CD8+ and tumor-infiltrating lymphocytes (TILs) for glioma, MB, ATRT and EPN methylation data.…”
Section: Targeting Immune Cells In Pediatric Brain Tumorsmentioning
confidence: 99%
See 1 more Smart Citation